Knowledge and attitude about evidence-based dental practice among dentists in Al-Kharj, Saudi Arabia - Inderjit M Gowdar; Faisal AlMrikhan; Fahad Alanazi; Khalid Alfaifi; Bashar Alanazi; Sami Al-Qahishi (Journal of Pharmacy and Bioallied Sciences, 2023)
Background: Quality of patient care will improve when dental professional practices are based on evidence. The present study was aimed at assessing the knowledge and attitude of private dental practitioners in Al-Kharj regarding evidence-based dentistry. Methodology: The study sample consisted of 180 private dental practitioners in Al-Kharj, Saudi Arabia. A pretested questionnaire was used to collect information regarding knowledge and attitude toward evidence-based dental practice (EBDP). Data were collected by direct personal contact and information was collected on the same day. Results: Awareness of EBDP among private dental practitioners was 67.8%. Also, 31.1% of subjects told that they practice EBD in decision-making about patient treatment. Only 16.7% of study subjects were aware of the Cochrane database, whereas 34.1% were aware of the evidence-based pyramid. Also, 91.7% thought that they needed to be trained regarding EBD. Conclusion: Awareness of EBDP is low among private dental practitioners but the majority of dentists think they need training regarding evidence-based dentistry.